2006
DOI: 10.3892/ijo.29.5.1075
|View full text |Cite
|
Sign up to set email alerts
|

Membrane vesicles shed by oligodendroglioma cells induce neuronal apoptosis

Abstract: Abstract. In order to investigate the mechanism by which oligodendrogliomas cause neuronal damage, media conditioned by G26/24 oligodendroglioma cells, were fractionated into shed vesicles and vesicle-free supernatants, and added to primary cultures of rat fetal cortical neurons. After one night treatment with vesicles, a reproducible, dose-dependent, inhibitory effect on neurite outgrowth was already induced and, after 48-72 h of incubation, neuronal apoptosis was evident. Vesicle-free supernatants and vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 69 publications
0
44
0
Order By: Relevance
“…Tumor cells of glial origin were recently shown to release extracellular vesicles that contain the FAS ligand and induce apoptosis in rat cortical neurons in culture (12). We also found that neurons themselves can shed large extracellular vesicles that contain angiogenic factors such as FGF-2 and VEGF (13).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Tumor cells of glial origin were recently shown to release extracellular vesicles that contain the FAS ligand and induce apoptosis in rat cortical neurons in culture (12). We also found that neurons themselves can shed large extracellular vesicles that contain angiogenic factors such as FGF-2 and VEGF (13).…”
Section: Resultsmentioning
confidence: 61%
“…As it has been recently found that some glial tumor cells (oligodendroglioma cells) (12) as well as primary neurons in culture (13) are able to release extracellular vesicles, we investigated the possibility that astrocytes can do the same. We found that indeed astrocytes produce extracellular structures that contain FGF-2 and VEGF, together with ß1-integrin, a membrane protein reported by other authors (see, for example: 14) to be a component of a heterogeneous population of large extracellular vesicles, ranging in size from 100-1000 nm called microvesicles (MVs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on oligodendroglioma cell cultures revealed that these cells shed MVs which inhibited neurite sprouting and caused apoptosis to primary fetal rat neurons, after 48-72 h of incubation (10). Proapoptotic effects of vesicles on neurons were dose-dependent and were induced also when concentrations of tumor-derived vesicles were similar to those probably occurring in vivo, when an oligodendroglioma tumor is growing inside the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 85%
“…This effect has been primarily attributed to compression on surrounding brain cells, caused by the increasing size of the tumor. More recently, it was suggested that G26/24 oligodendroglioma cells can actively induce neuronal damage by releasing molecules able to inhibit neurite sprouting and to eventually cause neuronal death (10). Interestingly, such molecules seem to be released through an unusual route involving shedding of extracellular membrane microvesicles (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation